2022
DOI: 10.3390/pharmaceutics14122636
|View full text |Cite
|
Sign up to set email alerts
|

Achievements in Mesoporous Bioactive Glasses for Biomedical Applications

Abstract: Nowadays, mesoporous bioactive glasses (MBGs) are envisaged as promising candidates in the field of bioceramics for bone tissue regeneration. This is ascribed to their singular chemical composition, structural and textural properties and easy-to-functionalize surface, giving rise to accelerated bioactive responses and capacity for local drug delivery. Since their discovery at the beginning of the 21st century, pioneering research efforts focused on the design and fabrication of MBGs with optimal compositional,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 226 publications
0
7
0
Order By: Relevance
“…In recent decades, it has been demonstrated that MBGs as drug carriers have the potential to repair bone defects, augment local drug concentrations, improve drug efficacy, reduce dosing frequency, and minimize side effects [ 29 , 30 ]. Quercetin, as a hydrophobic biologically active agent with low oral bioavailability and broad first-pass effect.…”
Section: Resultsmentioning
confidence: 99%
“…In recent decades, it has been demonstrated that MBGs as drug carriers have the potential to repair bone defects, augment local drug concentrations, improve drug efficacy, reduce dosing frequency, and minimize side effects [ 29 , 30 ]. Quercetin, as a hydrophobic biologically active agent with low oral bioavailability and broad first-pass effect.…”
Section: Resultsmentioning
confidence: 99%
“…Mesoporous bioactive glass (MBG) nanoparticles have been used for high drug load and targeted therapy approaches. Surface modification techniques, such as functionalization and composite production involving polymers and hydrogels, have been employed to enhance drug-release kinetics [ 233 ]. In one study, gold nanoparticles were incorporated into a BG–chitosan–gelatin composite, resulting in a significantly higher loading for the anticancer drug doxorubicin (DOX) compared to magnetic-core silica nanoparticles [ 234 , 235 ].…”
Section: Application Of Nanoparticles To Improve the Therapeutic Pote...mentioning
confidence: 99%
“…As a subgroup of BGs, MBGs are very versatile drug delivery vehicles thanks to their highly ordered porous structure (pore size between 2 and 50 nm) which provides a high SSA (Vallet-Regí et al, 2022). Although these biocompatible materials have been traditionally used in tissue engineering applications, MBGs, either magnetic or nonmagnetic, are now recognized as suitable candidates for cancer therapy.…”
Section: Nbgs For Anticancer Drug Deliverymentioning
confidence: 99%